2002
DOI: 10.1046/j.1524-4733.2002.52109.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Health-Care Decision Makers Find Economic Evaluations Useful? The Findings of Focus Group Research in UK Health Authorities

Abstract: Decision makers value information on cost-effectiveness as well as effectiveness alone, but methodological improvements are necessary to increase the reliability of economic studies. A quality-scoring system for published studies would be a useful development as a filtering mechanism for decision makers but would raise a number of challenges for health economists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 8 publications
(8 reference statements)
0
96
0
1
Order By: Relevance
“…This has been considered necessary because the use of health economics is not as widespread in France as it is in some other countries such as the UK. Research has confirmed this also to be a requirement of decision makers in the UK [9] and has invoked developments to NHS EED.…”
Section: Differences Between Nhs Eed and Codecsmentioning
confidence: 88%
See 1 more Smart Citation
“…This has been considered necessary because the use of health economics is not as widespread in France as it is in some other countries such as the UK. Research has confirmed this also to be a requirement of decision makers in the UK [9] and has invoked developments to NHS EED.…”
Section: Differences Between Nhs Eed and Codecsmentioning
confidence: 88%
“…The interpretation of economic evaluations may also be limited by the reader's knowledge of what constitutes good research so the relative strengths and weaknesses of economic evaluations may not be immediately obvious [7,8,9]. One response to these issues in healthcare decision making is the production of databases that identify,categorise,summarise and appraise published economic studies.In this field there are three established examples: the UK's NHS Economic Evaluation Database (NHS EED) [10,11,13], the Health Economic Evaluation Database (HEED, produced by the Office of Health Economics, London, UK), and France's Connaissances et Décision en ÉConomie de la Santé (CODECS) database [1].…”
Section: The European Network Of Health Economic Evaluation Databasesmentioning
confidence: 99%
“…Although others have advocated the wider use of pharmacoeconomics in formulary decisions, some barriers have been identified, such as, lack of locally relevant studies. [18][19][20][21] PHARMAC's provision of economic data and recommendations for targeting some new medicines, may have influenced the assessment processes. 22 We are currently studying the influence of individual economic assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Research in European countries indicates that, despite its growing importance, the use of economic evaluation in healthcare decision-making still remains rather limited and there is scope for a greater role [8][9][10][11][12]. However, further adoption of health economic evaluation from policy-makers collides on several challenges, at both a conceptual and practical level.…”
Section: Dimitrios Rovithismentioning
confidence: 99%
“…It has been advocated that decision-makers have gradually acquired the expertise that is necessary to appropriately interpret the results obtained from this kind of scientific ana lysis [103]. However, increasing amounts of evidence suggest that this is not really the case; decision-makers are being called to make decisions using scientific tools that they still do not really comprehend and are thus unable to immediately see the possible caveats of these studies that, in turn, guide their decisions [8][9][10][11][12].…”
Section: Dimitrios Rovithismentioning
confidence: 99%